Disruption and adaptation in response to the coronavirus pandemic – Assets as contextual moderators of enactment of health behaviours. Issue 3 (23rd March 2022) - Notley, Caitlin; Belderson, Pippa; Hanson, Sarah; Ward, Emma; Brown, Tracey J.; Naughton, Felix
Abstract : Purpose: During the COVID‐19 UK first national lockdown (March–July 2020) enactment of healthy behaviours was fundamentally changed due to social restrictions. This study sought to understand perspectives on health behaviour change, as part of a wider study tracking reported health behaviour change over time. Methods: A purposive sample was selected. N  = 40 qualitative interviews were conducted remotely (phone/video) from participants across England and Wales, and transcribed verbatim. Descriptive case studies were shared at regular analysis meetings. Inductive reflexive thematic coding was undertaken and coding was discussed using a team approach to agreeing analytical codes. A multiple lens theoretical perspective was adopted to illuminate the perceived influences and restrictions on participants' reports of health behaviour change. Results: There was a clear progressive narrative for all participants, through initial responses and reactions to the pandemic, framed as 'disruption', then, as lockdown was acclimatized to, evidence of 'adaptation'. Adaptation was seen in terms of modification, substitution, adoption, discontinuation/cessation, stultification, maintenance and recalibration of health behaviours. An illustrative case study exemplifies the narrative encompassing these features and demonstrating the complex non‐linear interactions between context and enacted health behaviours. Conclusions: Individuals responded to pandemic‐related social restrictions in complex ways. Those in contexts with existing social assets, community links and established patterns of healthy behaviours were able to respond positively, adapting by modifying behaviour and using technology to engage in healthy behaviours in new and innovative ways. For those in more vulnerable contexts, enacting (negative) health behaviour change was an expression of frustration at the limitations imposed by social restrictions.